Distance higher education; A review of digital tools for effective communication - et. al., Víctor Guido Flores-Ayala, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Distance professional training became as a necessary and effective method for students whose need is to be trained in a knowledge and that for different reasons do not have the possibility of attending the classroom in person. The use of digital tools is vital for the teaching-learning process and for the distance method to be effective and fulfill its purposes. In order to analyze the current context of the use of these tools, a bibliometric analysis was carried out to measure the scientific production of research works in the area of distance education, and a bibliographic analysis that allowed to obtain as a result, the main characteristics of what implies the use of digital tools for an effective communication in the development of distance higher education programs.